2010
DOI: 10.1073/pnas.0915018107
|View full text |Cite
|
Sign up to set email alerts
|

Differential release of chromatin-bound IL-1α discriminates between necrotic and apoptotic cell death by the ability to induce sterile inflammation

Abstract: IL-1α, like IL-1β, possesses multiple inflammatory and immune properties. However, unlike IL-1β, the cytokine is present intracellularly in healthy tissues and is not actively secreted. Rather, IL-1α translocates to the nucleus and participates in transcription. Here we show that intracellular IL-1α is a chromatin-associated cytokine and highly dynamic in the nucleus of living cells. During apoptosis, IL-1α concentrates in dense nuclear foci, which markedly reduces its mobile nature. In apoptotic cells, IL-1α … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
320
0
16

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 312 publications
(348 citation statements)
references
References 30 publications
(32 reference statements)
8
320
0
16
Order By: Relevance
“…In support of this model, we have shown that IL-33 is constitutively expressed to high levels in the nuclei of endothelial and epithelial cells in normal human tissues (27) and that it can be released in the extracellular space after cellular damage (23). Neutrophils are rapidly recruited into injured tissues during infection or in the absence of infection during "sterile inflammation," following the release of major alarmin molecules such as IL-1α and HMGB1 (28)(29)(30)(31)(32). After activation, they rapidly release serine proteases from cytoplasmic granules into the extracellular space (33).…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…In support of this model, we have shown that IL-33 is constitutively expressed to high levels in the nuclei of endothelial and epithelial cells in normal human tissues (27) and that it can be released in the extracellular space after cellular damage (23). Neutrophils are rapidly recruited into injured tissues during infection or in the absence of infection during "sterile inflammation," following the release of major alarmin molecules such as IL-1α and HMGB1 (28)(29)(30)(31)(32). After activation, they rapidly release serine proteases from cytoplasmic granules into the extracellular space (33).…”
Section: Discussionmentioning
confidence: 81%
“…We have previously proposed (23,27) that IL-33 may function as an endogenous danger signal or alarmin, similar to IL-1α and HMGB1 (28)(29)(30)(31)(32), to alert the immune system of cell or tissue damage during trauma or infection. In support of this model, we have shown that IL-33 is constitutively expressed to high levels in the nuclei of endothelial and epithelial cells in normal human tissues (27) and that it can be released in the extracellular space after cellular damage (23).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many intracellular cytokines, such as IL-1a and IL-33, are released upon cellular disintegration and serve as first-line alarmins to mediate signaling functions via their receptors on neighboring cells. 35,36 FAM19A4 is a potential alarmin that is initially induced during infections. Additionally, FAM19A4 was upregulated in the neuroendocrine CRI-G1 cell line upon mitochondrial and oxidative stress (GDS4014, GPL1355, 1378557_at) and in human brain endothelial cells in an in vitro model of cerebral malaria; 37 this further verifies that the expression of FAM19A4 is inducible in different tissues and cells.…”
Section: Fpr1 Is a Functional Receptor Of Fam19a4mentioning
confidence: 99%
“…Membrane IL-1α (ß23kDa) is thought to be immunostimulatory [11], while cytosolic proIL-1α controls homeostatic functions, such as gene expression and control of proliferation and differentiation [12]. IL-1α is not secreted and retained in cells during apoptosis process [13]. Necrosis-induced IL-1α activity is dependent on cell type and calpain cleavage.…”
mentioning
confidence: 99%